In vivo Morphometry of Inner Plexiform Layer (IPL) Stratification in the Human Retina With Visible Light Optical Coherence Tomography - Zhang, Tingwei; Kho, Aaron M.; Srinivasan, Vivek J. (Frontiers in Cellular Neuroscience, 2021)
From the bipolar cells to higher brain visual centers, signals in the vertebrate visual system are transmitted along parallel on and off pathways. These two pathways are spatially segregated along the depth axis of the retina. Yet, to our knowledge, there is no way to directly assess this anatomical stratification in vivo. Here, employing ultrahigh resolution visible light Optical Coherence Tomography (OCT) imaging in humans, we report a stereotyped reflectivity pattern of the inner plexiform layer (IPL) that parallels IPL stratification. We characterize the topography of this reflectivity pattern non-invasively in a cohort of normal, young adult human subjects. This proposed correlate of IPL stratification is accessible through non-invasive ocular imaging in living humans. Topographic variations should be carefully considered when designing studies in development or diseases of the visual system.